The lost intrinsic fragmentation of MAT1 protein during granulopoiesis promotes the growth and metastasis of leukemic myeloblasts. (4th October 2013) - Lou, Siyue; Liu, Gang; Shimada, Hiroyuki; Yang, Xiaochun; He, Qiaojun; Wu, Lingtao
ABSTRACT: MAT1, an assembly factor and targeting subunit of both cyclin‐dependent kinase‐activating kinase (CAK) and general transcription factor IIH (TFIIH) kinase, regulates cell cycle and transcription. Previous studies show that expression of intact MAT1 protein is associated with expansion of human hematopoietic stem cells (HSC), whereas intrinsically programmed or retinoic acid (RA)‐induced MAT1 fragmentation accompanies granulocytic differentiation of HSC or leukemic myeloblasts. Here we determined that, in humanized mouse microenvironment, MAT1 overexpression resisted intrinsic MAT1 fragmentation to sustain hematopoietic CD34+ cell expansion while preventing granulopoiesis. Conversely, we mimicked MAT1 fragmentation in vitro and in a mouse model by overexpressing a fragmented 81‐aa MAT1 polypeptide (pM9) that retains the domain for assembling CAK but cannot affix CAK to TFIIH‐core. Our results showed that pM9 formed ΔCAK by competing with MAT1 for CAK assembly to mimic MAT1 fragmentation‐depletion of CAK. This resulting ΔCAK acted as a dominant negative to inhibit the growth and metastasis of different leukemic myeloblasts, with or without RA resistance, by concurrently suppressing CAK and TFIIH kinase activities to inhibit cell cycle and gene transcription. These findings suggest that the intrinsically programmed MAT1 expression and fragmentation regulate granulopoiesis by inversely coordinating CAK and TFIIH activities, whereas pM9 shares a mechanistic resemblance with MAT1 fragmentation in suppressing myeloid leukemogenesis. Stem Cells 2013;31:1942‐1953